Application de la séquence éviter-réduire-compenser en France : le principe d’additionnalité mis à mal par 5 dérives - Harold Levrel; Fanny Guillet; Julie Lombard-Latune; Pauline Delforge; Nathalie Frascaria-Lacoste (VertigO)
The avoidong-minimizing-offseting sequence is becoming an increasingly important environmental policies in France over the past few years. The 2016 Law on the Recovery of Biodiversity has further strengthened the role of this public policy tool. In a context of an increasing mobilization of a diversity of stakeholders around this instrument, we observe five "drifts" that lead to creating a growing gap between the ambition of the no net loss goal of biodiversity mentioned in the texts and the application of the ERC sequence in the field : the implementation of ecological offsetting takes over the traditional tasks of the biodiversity conservation agencies ; the use of the offsetting fundings for the tradition conservation actions, without additionality principle, with the reinforcement of the financial disengagement of the State ; the use of public lands in order to facilitate the implementation of ecological offsetting ; the search of new economic rents for new stakeholders ; a competition system based on the lower cost goal.